Black sheep get the blues: A psychobiological model of social rejection and depression - Slavich, George M.; O’Donovan, Aoife; Epel, Elissa S.; Kemeny, Margaret E. (Neuroscience and biobehavioral reviews, 2010)
Major life events involving social rejection are strongly associated with onset of depression. To account for this relation, we propose a psychobiological model in which rejection-related stressors elicit a distinct and integrated set of cognitive, emotional, and biological changes that may evoke depression. In this model, social rejection events activate brain regions involved in processing negative affect and rejection-related distress (e.g., anterior insula, dorsal anterior cingulate cortex). They also elicit negative self-referential cognitions (e.g., “I’m undesirable,” “Other people don’t like me”) and related self-conscious emotions (e.g., shame, humiliation). Downstream biological consequences include upregulation of the hypothalamic–pituitary–adrenal axis, sympathetic–adrenal–medullary axis, and inflammatory response. Pro-inflammatory cytokines play an important role in this process because they induce a constellation of depressotypic behaviors called sickness behaviors. Although these changes can be short-lived, sustained inflammation may occur via glucocorticoid resistance, catecholamines, sympathetic innervation of immune organs, and immune cell aging. This response also may be moderated by several factors, including prior life stress, prior depression, and genes implicated in stress reactivity.